Here's the question you clicked on:
itsjustme_lol
Please help
If you were to use the substitution method to solve the following system, the expression equivalent to y from the second equation is substituted into the first equation.
2x – 7y = 4 3x + y = –17
Rearrange the second equation for y=.... then substitute that into the first and solve for x. Then substitute your x into any of the equations for solve for the value of y.
so ill get 2x – 7(3x – 17) = 4??
Almost. y=-3x-17 when you plug it in 2x-7(-3x-17)=4
shoot. alright, i appreciate it!
Post your x and y here if you need confirmation